First record of the family Heloridae (Hymenoptera: Proctotrupoidea) from Iran, with description of a new species - Izadizadeh, Mohammad; Talebi, Ali Asghar; Achterberg, Cornelis Van; Rakhshani, Ehsan (Zootaxa, 2015)
For the first time in more than 100 years, a new western Palaearctic species of Heloridae is described. Specimens of Helorus alborzicus Izadizadeh, van Achterberg & Talebi sp. nov. and Helorus ruficornis Förster were collected from the Alborz province of Iran. An illustrated identification key for Western Palaearctic Heloridae is provided.